RS 1.[083] : texte fragmentaire et énigmatique de la première campagne de fouilles à Ras Shamra-Ougarit (1929) - Pardee, Dennis (Syria, 2020)
RS 1.[083]: fragmentary, mysterious text from the first excavation campaign at Ras Shamra-Ugarit (1929)A new edition of a tablet fragment from the first season of excavations at Ras Shamra in 1929.